Anti-Corruption and Deradicalisation: Shaping a Generation with Integrity or Creating Apathetic Students? - Prayetno, Eko; Al Ayyubi, Ibnu Imam; Nurhikmah; Noerzanah, Firda; Saelaemae, Tasnim (CV. Gerasi Insan Nusantara, 2024)
This study aims to explore the impact of anti-corruption and de-radicalisation education on student character building, especially related to integrity and the potential for apathy. A qualitative method with in-depth interviews was used to explore the perspectives of students who have participated in these programmes. The results showed that although anti-corruption education and de-radicalisation increased students' awareness of the importance of integrity and the dangers of corruption, there were indications of the potential for apathy due to inconsistencies between the values taught and the reality faced. Differences in perceptions based on major background and personal experience also affect the effectiveness of the programme. Therefore, this research emphasises the need for a more contextual, participatory and sustainable approach in the implementation of anti-corruption and de-radicalisation education to maximise its impact in shaping a generation with integrity. By continuously improving the quality and effectiveness of anti-corruption and de-radicalisation education, we can build a more just, inclusive and prosperous future for future generations.